2018
DOI: 10.1002/cre2.98
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analyses of two bacterial sampling methods in ligature‐induced periodontitis in rats

Abstract: The prevalence profile of periodontal pathogens in dental plaque can vary as a function of the detection method; however, the sampling technique may also play a role in determining dental plaque microbial profiles. We sought to determine the bacterial composition comparing two sampling methods, one well stablished and a new one proposed here. In this study, a ligature‐induced periodontitis model was used in 30 rats. Twenty‐seven days later, ligatures were removed and microbiological samples were obtained direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…One approach to simulate human PD in vertebrate animals is to generate subgingival biofilm retentive milieus by placing silk ligatures inside gingival sulci of molars, which facilitate the onset of inflammation mediated alveolar bone loss . Changes in ligature‐associated biofilms show similar microbial shifts to humans with PD compared to health . The ligature model has been used in rodents and larger vertebrates including dogs or nonhuman primates such as rhesus monkeys, cynomolgus monkeys, and baboons due to similarities with oral human structures that facilitate naturally occurring dental plaque, calculus, putative human periodontal pathogens, and PD .…”
Section: Experimental Pd Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to simulate human PD in vertebrate animals is to generate subgingival biofilm retentive milieus by placing silk ligatures inside gingival sulci of molars, which facilitate the onset of inflammation mediated alveolar bone loss . Changes in ligature‐associated biofilms show similar microbial shifts to humans with PD compared to health . The ligature model has been used in rodents and larger vertebrates including dogs or nonhuman primates such as rhesus monkeys, cynomolgus monkeys, and baboons due to similarities with oral human structures that facilitate naturally occurring dental plaque, calculus, putative human periodontal pathogens, and PD .…”
Section: Experimental Pd Modelingmentioning
confidence: 99%
“…43 Changes in ligature-associated biofilms show similar microbial shifts to humans with PD compared to health. 44,45 The ligature model has been used in rodents and larger vertebrates including dogs or nonhuman primates such as rhesus monkeys, cynomolgus monkeys, and baboons due to similarities with oral human structures that facilitate naturally occurring dental plaque, calculus, putative human periodontal pathogens, and PD. 46,47 However, larger vertebrates are less frequently used due to ethical and economic constraints, and experimental PD in rodents using ligatures or pathogen inoculation do not fully reproduce human PD.…”
Section: F I G U R E 1 Overview Of the Effector Cells In The Pathogenmentioning
confidence: 99%
“…Belibasakis and colleagues [ 27 ] reported similar profiles of ‘Red complex’ both from paperpoint and from curette samples. In another study, ligature that induced experimental periodontitis and paperpoint subsequently inserted in the same sites after ligature removal were compared with checkerboard DNA-DNA hybridization [ 28 ]. Considering that similar bacterial profiles between the ligature and paperpoint, it is suggested that a ligature on a tooth may also be used as a sampling method.…”
Section: Discussionmentioning
confidence: 99%